High-level N/P co-doped Sn-carbon nanofibers with ultrahigh pseudocapacitance for high-energy lithium-ion and sodium-ion capacitors. (1st November 2020) - Yang, Cheng; Ren, Jianguo; Zheng, Mingsen; Zhang, Mengyan; Zhong, Zheng; Liu, Ruoqi; Huang, Jian; Lan, Jinle; Yu, Yunhua; Yang, Xiaoping
Abstract: The development of high-energy lithium-ion and sodium-ion capacitors (LICs and SICs) is still a challenge due to the kinetics mismatch between the insertion/deinsertion anode and adsorption/desorption cathode. Here, high-level N/P-doped Sn-carbon nanofibers (Sn-NP-CNFs) were fabricated via an electrospinning technique followed by pre-oxidization and carbonization. The N/P-doping increased the defects and carbon interlayer distance to inhibit the precipitation and volume expansion of the Sn and improve the Li/Na-adsorption, resulting in an ultrahigh pseudocapacitance and rate capability of the Sn-NP-CNF. An advanced LIC and SIC were composed of an activated carbon cathode and a Sn-NP-CNF anode. The LIC and SIC displayed ultrahigh energy densities (186.0 Wh kg −1 and 134.6 Wh kg −1 ) and power densities (20.0 kW kg −1 achieved at 22.2 Wh kg −1 ) with superior energy retentions (83.7% and 79.8% after 10, 000 cycles at 5.0 A g −1 ).